Effect of gibberellic acid on photosynthesis and oxidative stress response in maize under weak light conditions - Fu, Jianjun; Li, Linlin; Wang, Shuang; Yu, Na; Shan, Hong; Shi, Zhensheng; Li, Fenghai; Zhong, Xuemei (Frontiers in Plant Science, 2023)
Gibberellin (GA) is an important endogenous hormone involved in plant responses to abiotic stresses. Experiments were conducted at the Research and Education Center of Agronomy, Shenyang Agricultural University (Shenyang, China) in 2021.We used a pair of near-isogenic inbred maize lines comprising, SN98A (light-sensitive inbred line) and SN98B (light-insensitive inbred line) to study the effects of exogenous gibberellin A3 (GA3) application on different light-sensitive inbred lines under weak light conditions. The concentration of GA3 was selected as 20, 40 and 60 mg L-1. After shade treatment, the photosynthetic physiological indexes of SN98A were always lower than SN98B, and the net photosynthetic rate of SN98A was 10.12% lower than SN98B on the 20th day after shade treatment. GA3 treatments significantly reduced the barren stalk ratios in SN98A and improved its seed setting rates by increasing the net photosynthetic rate (Pn), transpiration rate (Tr), stomatal conductance (Gs), photosynthetic pigment contents, photochemical efficiency of photosystem II (PS II) (Fv/Fm), photochemical quenching coefficient (qP), effective quantum yield of PSII photochemistry (ΦPSII), and antioxidant enzyme activities, where the most effective treatment was 60 mg L–1GA3. Compared with CK group, the seed setting rate increased by 33.87%. GA3 treatment also regulated the metabolism of reactive oxygen species (ROS) and reduced the superoxide anion (O2-) production rate, H2O2 content, and malondialdehyde content. The superoxide anion (O2-) production rate, H2O2 content and malondialdehyde content of SN98A sprayed with 60 mg L-1 GA3 decreased by 17.32%,10.44% and 50.33% compared with CK group, respectively. Compared with the control, GA3 treatment significantly (P < 0.05) increased the expression levels of APX and GR in SN98A, and APX, Fe-SOD, and GR in SN98B. Weak light stress decreased the expression of GA20ox2, which was related to gibberellin synthesis, and the endogenous gibberellin synthesis of SN98A. Weak light stress accelerated leaf senescence, and exogenous GA3 application inhibited the ROS levels in the leaves and maintained normal physiological functions in the leaves. These results indicate that exogenous GA3 enhances the adaptability of plants to low light stress by regulating photosynthesis, ROS metabolism and protection mechanisms, as well as the expression of key genes, which may be an economical and environmentally friendly method to solve the low light stress problem in maize production.